Association between smoking status and handgrip strength in Korean male adults: based on Korea National Health and Nutrition Examination Survey 2016–2019 - Cho, Eunbyul; Soh, Hi Sun; Lee, Jae-Ryun; Yun, Jieun; Bae, Woo Kyung; Lee, Hyejin (Frontiers in Medicine, 2023)
Background Smoking is a well-known risk factor of frailty. Handgrip strength (HGS) is highly representative of muscular strength and is used in the diagnosis of frailty; however, the relationship between smoking and HGS is not clear. We evaluated the relationship between smoking status and HGS. Objectives This study aimed to evaluate the association between HGS and smoking status. Methods We enrolled adult males between the ages of 19 and 80 years who participated in the Korea National Health and Nutrition Examination Survey VII–VIII. A chi-square test and ANOVA were performed to compare the mean handgrip strength (mean HGS) between non-smokers, ex-smokers, and current smokers. Logistic regression analysis was performed to determine the association between the smoking status and mean HGS, and additional analyses were performed by dividing subgroups by age. Results A total of 7,649 participants were analyzed. When the mean HGS and mean dominant HGS were compared according to smoking status, HGS was higher in the right hand (value of p = 0.03) and left hand (value of p < 0.001) in the order of current smokers, ex-smokers, and non-smokers. Comparing HGS of stronger hands, the mean HGS ex-smokers [aOR, (95% confidence interval): 0.61 (0.46–0.82)] and current smokers: 0.55 (0.38–0.78) was higher than that of non-smokers. When subgroup analysis was performed according to age, current smokers aged >60 years had a higher grip strength than non-smokers. Conclusion Current smokers had a stronger mean HGS than that of ex-smokers and non-smokers. Current smokers older than 60 years appeared to have a stronger mean HGS than ex-smokers and non-smokers of the same age group.